Irrlicht 1.7 realtime 3D engine : beginner's guide : create complete 2D and 3D applications with this cross-platform, high performance engine /: beginner's guide : create complete 2D and 3D applications with this cross-platform, high performance engine. (2011) - Unknown
No abstract available